Endoscopic treatment of esophageal strictures About 380 dilations in 129 patients New instruments - de Simone, Gustavo H; Piazze, Alvaro; Boccardo, Carlos; Zimmer, Walter (Cirugía del Uruguay, 1994)
Endoscopic dilations of esophagica/ stenosis of various etiologies constitute transient or definitive pal/iative treatment according to the circumstances. The usage of operative fibroendoscopy makes possible secure, ambulatoria/ sessions with no general anesthesics, and it is of e/ection as opposed to rigid endoscopy. The authors present the 10 year experience (1980-1990) of 380 dilation sessions in 129 patients. They analyse indications, material, method and results, and arrive to